Micro Insurance Awareness in Rural India - Mohanasundari M; Gurunathan K, Balanaga (Journal of Commerce and Trade, 2010)
The insurance sector in India has experienced a 360-degree journey over a period of more than a hundred years. Confidently by an ability to provide life insurance protection to nearly two people per second, the need for awareness of risk and education in the insurance sector is securing excellent progress. Dealing with Micro insurance and the representation is a mere dot on the work of art. With the obvious obstructions for low risk awareness in Rural India ranging from individual receptiveness towards risk exposure, consumer short-term style of living, each link in this tough chain seems indestructible. At a condemnatory level, a chain is as strong as its weakest bond and the weakest obstacle to break in this scenario is to relearn the lesson, as described by management experts, that there are undiscovered rupee coins sprinkled around the rural India, ready to be picked up, if have the know-how. This paper tries to explore the unique initiatives and potential for modernism to raise risk awareness and education of micro insurance in rural India. And so begins the journey to discover, discard and relearn.